Mindful Self-Compassion (MSC) Training to Improve the Subjective Well-Being of Postpartum Women After Caesarean Delivery - Rahayu, Fahmi Windia; Riasnugrahani, Missiliana; Victoriana, Evany (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2025)
Postpartum women experience both physical and psychological changes. Previous studies have shown that women who delivered via caesarean section tend to have lower levels of Subjective Well-Being (SWB) than those who gave birth vaginally. If left unaddressed, these psychological challenges may lead to anxiety or depression. This study aimed to investigate the impact of Mindful Self-Compassion (MSC) training on improving the Subjective Well-Being of postpartum women following caesarean delivery. This research employed a randomized controlled pilot trial (waitlist control) with pretest–posttest assessments and utilized non-parametric analysis (Mann-Whitney U Test). The Scale of Positive and Negative Experience (SPANE), Satisfaction with Life Scale (SWLS), and Self-Compassion Scale (SCS) were used to measure Subjective Well-Being and self-compassion. The results showed a significant increase in Subjective Well-Being among participants in the experimental group after receiving the MSC training. The findings suggest that MSC training is effective in improving the well-being of postpartum women who delivered via caesarean section.